Monetary policy transmission through the bank-financing channel in Malaysia: Evidence from bank-level data - Asbeig, Hussam I.; Kassim, Salina (Statistical Economic and Social Research and Training Centre for Islamic Countries, 2014)
This study analyses the role of Islamic banks in transmitting monetary policy through the bank-financing channel in Malaysia. Bank size, liquidity and capitalization levels are hypothesized to be sources of cross-sectional differences among banks. If relevant, this implies that the financing channel is operational through the Islamic banks. We evaluate a sample period from 2000 to 2011, using panel data with robust standard errors, to investigate the heterogeneity of the financing supply in response to monetary policy shocks. The results show no significant differences across banks, based on size, capitalization and liquidity levels, and thus do not support the presence of a bank-financing channel in Malaysia. The study contributes a deeper understanding of the role of Islamic banks in the monetary policy transmission mechanism in Malaysia